2013
DOI: 10.1080/01419870.2013.790983
|View full text |Cite
|
Sign up to set email alerts
|

Cricket, drinking and exclusion of British Pakistani Muslims?

Abstract: Throughout history sports cultures and alcohol have been intimately linked. Being able to drink huge amounts of alcohol is a celebrated male athletic virtue. Ridicule and often exclusion is reserved for those who are unable to conform to this. Ritualised drinking is not, and cannot, be enjoyed by all. British Muslims (the majority of whom are of South Asian descent) for instance, are restricted from drinking alcohol due to the demands of Islam. This paper uses data collected from ethnographic research conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 31 publications
2
26
0
1
Order By: Relevance
“…One conduit through which the interplay between old and new homes was reproduced was through the love of sport many brought with them (Fletcher and Spracklen 2013). For many members of the South Asian diaspora, there exists a continuation of ethnic solidarities and attachments to the symbols of national belonging and continuing investment, emotionally, economically and culturally in the 'homeland'.…”
Section: Pakistani Migration To the Uk And Norwaymentioning
confidence: 99%
“…One conduit through which the interplay between old and new homes was reproduced was through the love of sport many brought with them (Fletcher and Spracklen 2013). For many members of the South Asian diaspora, there exists a continuation of ethnic solidarities and attachments to the symbols of national belonging and continuing investment, emotionally, economically and culturally in the 'homeland'.…”
Section: Pakistani Migration To the Uk And Norwaymentioning
confidence: 99%
“…See http://www.guardian.co.uk/world/2010/oct/18/ pakistan-isi-mumbai-terror-attacks 3. See Fletcher and Spracklen (2013) for a discussion of sport and drinking, and the tension that exists within the South Asian community, particularly Pakistani Muslims. 4.…”
Section: Notesmentioning
confidence: 99%
“…Long et al 2009), including: low incomes; long working hours; religious observance; shortage of facilities in ethnic areas; language barriers and racism(s) (Hylton et al 2015). It has also been suggested that there are cultural barriers to participation in sport; in particular with regards to diet and drinking (Fletcher & Spracklen, 2014). Cricket is rather different.…”
Section: Cricket and South Asian Communitiesmentioning
confidence: 99%